2019
DOI: 10.1111/nmo.13761
|View full text |Cite
|
Sign up to set email alerts
|

Epiphrenic diverticula: An added source of complexity in achalasia management

Abstract: Epiphrenic (pulsion) esophageal diverticula can occur in the setting of underlying esophageal motility disorders such as achalasia and present a unique management challenge to the gastroenterologist. Asymptomatic diverticula do not require treatment, but symptomatic diverticula require therapy targeted to the underlying esophageal motility disorder, or else the diverticula will recur. Generally, laparoscopic or combined laparoscopic/thoracoscopic myotomy, diverticulectomy, and anterior fundoplication are requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…No difference in perioperative complications in patients with and without epiphrenic diverticula was observed [8]. Further, only small case series and case reports are published that concluded that POEM without diverticulotomy was safe and effective as treatment for patients with an esophageal diverticulum [17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No difference in perioperative complications in patients with and without epiphrenic diverticula was observed [8]. Further, only small case series and case reports are published that concluded that POEM without diverticulotomy was safe and effective as treatment for patients with an esophageal diverticulum [17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a small number of studies have investigated the efficacy and safety of POEM without diverticulotomy in patients with esophageal diverticula and are limited by the number of included patients [17][18][19][20][21][22][23][24][25][26]. The largest study thus far with fourteen patients showed a decrease in Eckardt score after POEM.…”
Section: Introductionmentioning
confidence: 99%
“…The low recurrence rate of our study may be associated with a shorter follow-up period and consolidated definitions of recurrence. Epiphrenic diverticula are commonly associated with esophageal motility disorders, so the management of epiphrenic diverticula requires addressing the underlying motility disorders; otherwise, the diverticula may recur after diverticulectomy [31]. It is considered that in patients with epiphrenic diverticulum with esophageal motility disorders, POEM through the gastroesophageal junction may pose a higher risk of gastroesophageal reflux than laparoscopic myotomy with fundoplication [32].…”
Section: Discussionmentioning
confidence: 99%